Finland : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that Finland's economy has made a strong recovery from the deep recession that began in the early 1990s. Spurred by a devaluation of the markka, growth was predominantly export driven, and the external current account shifted from a deficit of more than 5 percent in the early 1990s to a surplus of the same magnitude in 1997/98. In this setting, prudent macroeconomic policies brought public finances from a deficit of 7 percent of GDP in 1993 to a surplus in 1998.